DISTRIBUTION OF DNA DAMAGE REPAIR GENE POLYMORPHISM hOGG1, XRCC1 and p53 AMONG SICKLE CELL DISEASE PATIENTS IN INDIA - Sudhansu Sekhar Nishank (Mediterranean Journal of Hematology and Infectious Diseases)
Background– Defect in DNA damage repair genes due to oxidative stress predispose the humans to malignancies. There are many cases of association of malignancies with sickle cell disease patients (SCD) throughout the world, the molecular cause of which has never been investigated. DNA damage repair genes such as  hOGG1, XRCC1 and p53 play significant role in repair of DNA damage during oxidative stress but the distribution and clinical effect of these genes are not known till date in SCD patients who are associated with oxidative stress related clinical complications.